The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3390/risks3030420
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Stress Index: Identification of Systemic Risk Conditions

Abstract: This paper develops a financial stress measure for the United States, the Cleveland Financial Stress Index (CFSI). The index is based on publicly available data describing a six-market partition of the financial system comprising credit, funding, real estate, securitization, foreign exchange, and equity markets. This paper improves upon existing stress measures by objectively selecting between several index weighting methodologies across a variety of monitoring frequencies through comparison against a volatili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 46 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…• Kansas City Financial Stress Index (KCFSI) (Hakkio -Keeton 2009) • Financial Stress Indicator of Canada (FSI) (Illing -Liu 2006) • Composite Indicator of Systemic Stress (CISS) (Holló et al 2012) • Cleveland Financial Stress Index (CFSI) (Oet et al 2015).…”
Section: Stresszmentioning
confidence: 99%
“…• Kansas City Financial Stress Index (KCFSI) (Hakkio -Keeton 2009) • Financial Stress Indicator of Canada (FSI) (Illing -Liu 2006) • Composite Indicator of Systemic Stress (CISS) (Holló et al 2012) • Cleveland Financial Stress Index (CFSI) (Oet et al 2015).…”
Section: Stresszmentioning
confidence: 99%
“…Building on the research precedent of Liu (2003, 2006), Oet et al (2009Oet et al ( , 2011 define systemic risk as a condition in which the observed movements of financial market components reach certain thresholds and persist. They develop the financial stress index in the U.S. (CFSI) 13 as a continuous index constructed of daily public market data.…”
Section: Measuring Financial Stress -Dependent Variable Datamentioning
confidence: 99%
“…To conserve space, the tables show only information for the explanatory variables that ultimately enter the SAFE model. markets' stress series by Oet et al (2009Oet et al ( , 2011. The present paper contributes a new typology for the drivers of risk in the EWS; its risk model applies a regression approach to explain the financial markets' stress index using optimally lagged institutional data.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The US Federal Reserve Banks of St. Louis, Kansas and Cleveland remain the pioneers of stress indices. The Cleveland stress index created by Oet et al (2011) parsimoniously represents the trends and dynamics of numerous United States stress indicating variables. Our index is the first of its kind based on UK financial markets.…”
Section: Introductionmentioning
confidence: 99%